8‐12 GHz single‐input GaN load modulated balanced amplifier monolithic microwave integrated circuit. Issue 5 (9th February 2022) - Yin, Zheng; Tao, Hong‐Qi; Wang, Guangnian; Guo, Runnan
Abstract: In this article, a broadband single‐input GaN load modulated balanced amplifier (LMBA) with prematching networks is presented. The prematching networks of main PA are set up to reduce the difficulty of load modulation caused by high power control signal. The compact phase shifter and compression characteristic of the CS PA are used to monolithically integrate a single‐input LMBA. The experimental results under continuous wave demonstrate a peak output power of 43.1–43.6 dBm, with drain efficiency (DE) of 49%–54% over the band of 8–12 GHz. Moreover, the DE is in the range of 30%–37% at the 6‐dB power back‐off region. By introducing a 16‐quadrature amplitude modulation signal with 6‐dB peak‐to‐average power ratio, the proposed single‐input LMBA monolithic microwave integrated circuit achieves better than −28‐dBc adjacent channel leakage ratio and higher than 32% average DE without digital predistortion at 9 and 11 GHz.